2017
DOI: 10.1021/acs.macromol.7b01594
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in Ionic Liquid–Cellulose Solutions during Coagulation in Water: Mass Transport and Coagulation Rate Measurements

Abstract: This article describes central features of the mass transport during the coagulation in water of cellulose–1-ethyl-3-methyl­imidazoium acetate ([C2mim]­[OAc]) solutions, namely, that the diffusivities are mainly affected by the relative concentrations of water and [C2mim]­[OAc], that the concentration of cellulose does not affect diffusivities and coagulation rates, that the diffusivities of low-M w compounds are similar to those in aqueous [C2mim]­[OAc] solutions without macromolecules, that the polymer conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…A critical review of the literature data is available in recent report by Hedlund et al (2017). The reported value of diffusion coefficient of water and NMMO in NMMO/cellulose dope measured by visual inspection of diffusion front (Biganska2005), after correction of equation as pointed out by Hedlund et al (multiplication by factor of 4), was 4.4×10 -9 m 2 /s, which is higher than the selfdiffusion coefficient of water at ambient conditions (2.57×10 -9 m 2 /s).…”
Section: Introductionmentioning
confidence: 99%
“…A critical review of the literature data is available in recent report by Hedlund et al (2017). The reported value of diffusion coefficient of water and NMMO in NMMO/cellulose dope measured by visual inspection of diffusion front (Biganska2005), after correction of equation as pointed out by Hedlund et al (multiplication by factor of 4), was 4.4×10 -9 m 2 /s, which is higher than the selfdiffusion coefficient of water at ambient conditions (2.57×10 -9 m 2 /s).…”
Section: Introductionmentioning
confidence: 99%
“…Based on comparisons of the SEM images of different samples, it is apparent that the material that was coagulated from the 5 wt% cellulose solution is denser than expected. A previous study (Hedlund et al 2017) found that the dry content of the cellulose structure before solvent exchange and drying correlates with each solution's cellulose concentration. This indicates that the 5 wt% cellulose material underwent a large degree of volume collapse during solvent exchange and drying, which disqualifies it from the general comparison of pore structures observed using SEM.…”
Section: Sem Imagesmentioning
confidence: 95%
“…Coagulation was performed by covering a steel rod (diameter of 4 mm) with a 0.35 mm thick solution layer and immersing the rod in water or 2PrOH for a sufficient amount of time to coagulate the full layer thickness, cf. (Hedlund et al 2017). The resulting cellulose tube (* 0.3 g wet) was pulled off the rod and stored in a small flask with about 4 ml of the coagulant used.…”
Section: Coagulationmentioning
confidence: 99%
“…Those changes in the mechanical properties might be related to changes in the kinetics of the coagulation and regeneration steps, which rates would be directly affected by the amount of IL in the bath. 3,7,12 Crystalline structure of the spun fibers Background corrected intensity profiles from 0, 15, 30, 45, and 60 IL concentration at DR 3 are shown in Figure S6 in the ESI. No shift was observed for the peak position by different IL concentrations, indicating the identical cellulose II crystal structure for all the IL concentrations in the spin bath.…”
Section: Fiber Properties As a Function Of The Bath Compositionmentioning
confidence: 99%
“…The cellulose filaments regeneration kinetic is controlled by the relative diffusive fluxes of the solvent (IL) from the solution into the bath and the nonsolvent (H 2 O) from the bath into the gradually forming filament 3 . 7 The diffusive fluxes of the solvent and nonsolvent are proportional to the concentration gradients between the incipient filament and the bath. In addition, the diffusivities of the cation and anion in a H 2 O/IL mixture may change with the water mole fraction in the coagulation bath 8 .…”
Section: Introductionmentioning
confidence: 99%